PERAN KECERDASAN EMOSIONAL PUSTAKAWAN DALAM MENINGKATKAN KUALITAS LAYANAN PERPUSTAKAAN - Unyil, Unyil; Pauzi, Pauzi (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2025)
The role of librarians as the frontline in interacting with users, exploring how emotional intelligence can help librarians understand user needs, manage challenges that arise, and create satisfying service experiences. The purpose of writing this article is to explore the role of librarian emotional intelligence in improving the quality of library services. Providing a deeper understanding of how emotional intelligence, which includes the ability to recognize, manage, and utilize emotions effectively, is a key factor in improving the quality of library services. The method applied in this writing applies a qualitative method by utilizing a literature review that discusses the Role of Librarian Emotional Intelligence in Improving the Quality of Library Services. Librarians need to have the ability to manage their emotions, so that they can create positive emotions and build good relationships with users. Librarians with high levels of emotional intelligence are able to build better relationships through users, increase their satisfaction, and strengthen the positive image of the library. Emotional intelligence also helps librarians in dealing with work pressure, managing stress, and remaining productive even in challenging situations. Therefore, it is important for library managers to realize the importance of developing librarian emotional intelligence as part of a service improvement strategy.